Additive Engineering toward High‐Performance Tin Perovskite Solar Cells. Issue 5 (17th March 2021) - Wu, Tianhao; Cui, Danyu; Liu, Xiao; Luo, Xinhui; Su, Hongzhen; Segawa, Hiroshi; Zhang, Yiqiang; Wang, Yanbo; Han, Liyuan
Abstract : Perovskite solar cells (PSCs) have emerged as one of the third‐generation photovoltaic technologies. However, the toxicity issue of the lead element in perovskite absorbers hinders their large‐scale production. Thus, exploiting lead‐free perovskite materials becomes an important solution to overcome this challenge. Among all the candidates, tin perovskites have advanced rapidly in recent years due to their low toxicity, favorable bandgap, and high carrier mobility. After a few years of development, the highest power conversion efficiency (PCE) of tin PSCs has exceeded 13%, which is mainly attributed to the breakthroughs arising from additive engineering of the Sn perovskite layer. Herein, the role of additive engineering in the research community of tin PSCs is emphasized. First, the crystal structure, electronic characteristics, and the chemical instability of Sn perovskites are introduced. Next, additives used for stabilizing the Sn 2+ components, purifying SnI2 sources, and improving the crystal quality of perovskite films are discussed in detail. Finally, challenges and perspectives are laid out to advance the properties of tin halide perovskites for further improving the device efficiency and stability. Abstract : The application of additive engineering in tin perovskite solar cells is reviewed, from the aspects of the structures and properties of tin perovskite, additives used for stabilizing divalent Sn 2+, purifying the tin source to improving the crystalline quality. In addition, challenges and perspectives are proposed to promote the performance of tin perovskite solar cells.